Social Media Marketing in Tourism: A study of visitor attractions in the Thanet Area - Palmer, Emma (2015)
This research study aims to identify issues relating to Social Media Marketing in the Tourism sector. The study concentrates its research to tourist visitor attractions in the Thanet region of the United Kingdom; specifically museum attractions in the seaside towns of Margate, Broadstairs and Thanet. The study further aims to seek recommendations for improving Social Media Marketing for this sector. Three research questions have been put forward in relation to the value Social Media Marketing has on the wider Marketing context. The Thanet area was chosen for the purpose of this study because there is no published research in relation to Social Media Marketing in this region. There has however been a high media spotlight on parts of the Thanet area as a result of an injection of funds from the Government and a resurgence of visitors to British seaside towns A simple research method was used underpinned by a qualitative approach. This included 5 depth interviews with museums in the study area. This allowed for a deep understanding of current practices, strategies and challenges such organisations in the study area had in relation to Social Media Marketing. In analysis of the results, several common themes have been identified and resource to support Social Media Marketing appears to be a fundamental issue. Social Media Marketing presents an opportunity to effectively engage, sustain and grow an organisations visitor numbers. It is clear that Social Media Marketing holds various weights of value amongst organisations and where it is given more value, better results and resource are dedicated to it. Managers and those accountable for marketing strategies in attractions are recommend to review the current status as part of wider business plans.